Patient safety culture and identify factors associated with positive attitudes in private dental hospitals using the Indonesian Safety Attitude Questionnaire (SAQ-Indo): a cross-sectional study - Juliawati, Mita; Arbianti, Kusuma; Juslily, Marta; Anggraini, Wita; Gusbela, Balqis I; Astoeti, Tri Erri (Padjadjaran Journal of Dentistry, 2025)
Introduction: Patient Safety culture (PSC) in healthcare represents a significant challenge on a global scale. However, in Indonesia data on the PSC among dental healthcare workers remain limited and knowledge about PSC among dental healthcare personnel is still insufficient. Consequently, there is a necessity for education and additional knowledge on this matter.  This study aims to analyze the patient safety culture among dental healthcare workers and identify factors associated with positive attitudes in private dental hospitals using the Indonesian Safety Attitude Questionnaire (SAQ-Indo) Methods: A descriptive observational cross-sectional study design was used. The study was conducted among dental healthcare workers in two private dental hospitals in Jakarta and Semarang, Central Java. PSC factors were identified using bivariate analysis with Chi-square and simple logistic regression which classified responses as positive or negative based on the median of total score. The PSC score was the total score from 30 SAQ-Indo questions. Results: This study identified low, medium, good and very good safety culture levels based on percentile classification. Positive attitudes toward patient safety were found among participants from both private dental hospitals. Several factors were found to be associated with positive attitudes toward patient safety, including type of dental healthcare workers, age, level of education and practical experience. Conclusion: This study revealed patient safety attitudes among dental healthcare workers. The positive PSC scores were around 45% for the hospital in Jakarta and 32% for the hospital in Central Java. There is a need for socialization and education on PSC for dental healthcare workers at both private dental hospitals. Several factors were also found to be associated with positive attitudes toward patient safety, including professional role, age, educational level, and clinical experience. These findings may help increase awareness of patient safety at the hospital level in the future